Geological survey party, Mascot, Sydney (1934)
"In September and October 1934 a geological survey party made up of representatives from the Western Australia, Queensland, and Commonwealth governments flew over extensive ares of northern Australia to carry out aerial reconnaisance as a preliminary to ground geological surveys."--Information from accompanying material.
From L to R: P.B. Nye (Tasmanian Government Geologist) Frank Forman (Western Australian Government Geologist), Alan Hooper (wireless operator), Pat Hall (chief pilot), Harry Purvis (relief pilot and mechanic), Dr. W.G. Woolnough (Commonwealth Geological Adviser), Mrs Woolnough, Sir Charles Kingsford Smith, and A.C. Smith (Secretary to executive committee). L.C. Ball (Queensland Government Geologist) joined the party at Brisbane.
Title from accession record and accompanying material.
This is a copy negative made by the National Library of Australia from an original in private ownership.
Keywords: Aerial, Geological and Geophysical Survey of Northern Australia; Geologists -- Australia -- Portraits; Geological surveys -- Australia